Bimbingan Berbasis Real Life System (RLS) untuk Mengembangkan Pola Pikir Anak yang Mengalami Deprivasi Budaya - Euis Nurhidayati; Fatchiah E.Kertamuda (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Cultural deprivation develops more in deprivation and disadvantage environments, discussions and research on cultural deprivation in educational settings are still relatively few. This study aims to obtain a formulation of real life guidance (real life system) as a guidance system in schools that is friendly to cultural deprivation, as well as efforts to develop the mindset of children who experience cultural deprivation. The research method used is mixed method sequential explanatory, namely quantitative analysis followed by qualitative analysis to strengthen quantitative results. Participants in this study consisted of collaborators, namely: (1) all teachers and (2) parents whose children were selected as participants, while the research participants consisted of 16 (sixteen) students who had activities outside of school (work). The real life guidance model (real life system (RLS)) was declared effective in developing the mindset of children who experience cultural deprivation, supported by teacher skills both in implementing guidance and RLS-based learning, and parents who are more attentive and concerned about their children's education.